High prevalence of obesity among women in urban Haiti: Findings from a population-based cohort - Dade, Eliezer; Metz, Miranda; Pierre, Jean Lookens; Rouzier, Vanessa; Sufra, Rodney; Fox, Elizabeth; Preval, Fabyola; St-Preux, Stephano; Zephir, Jean Ronald; Ariste, Wilson; Rasul, Rehana; Sabwa, Shalom; et al. (Frontiers in Public Health, 2022)
Introduction Obesity is associated with increased risk of non-communicable diseases and death and is increasing rapidly in low- and middle-income countries, including Haiti. There is limited population-based data on body mass index (BMI) and waist circumference (WC) and associated risk factors in Haiti. This study describes BMI and WC, and factors associated with obesity using a population-based cohort from Port-au-Prince. Methods Baseline sociodemographic and clinical data were collected from participants in the Haiti CVD Cohort Study between March 2019 - August 2021. Weight was categorized by BMI (kg/m2) with obesity defined as >30kg/m2. Abdominal obesity was defined using WC cutoffs of ≥80cm for women and ≥94 cm for men based on WHO guidelines. Sociodemographic and behavioral risk factors, including age, sex, educational attainment, income, smoking status, physical activity, fat/oil use, daily fruit/vegetable consumption, and frequency of fried food intake were assessed for their association with obesity using a Poisson multivariable regression. Results Among 2,966 participants, median age was 41 years (IQR: 28-55) and 57.6% were women. Median BMI was 24.0 kg/m2 (IQR: 20.9 - 28.1) and 508 (17.1%) participants were obese. Women represented 89.2% of the population with BMI >30 kg/m2. A total of 1167 (68.3%) women had WC ≥80cm and 144 (11.4%) men had WC ≥94cm. BMI >30 kg/m2 was significantly more prevalent among women than men (PR 5.7; 95% CI: [4.3-7.6]), those 40-49 years compared to 18-29 years (PR 3.3; 95% CI: [2.4-4.6]), and those with income >10 USD per day compared to <1 USD (PR 1.3; 95% CI: [1.0-1.6]). There were no significant associations with other health and behavioral risk factors. Discussion In Haiti, women have an alarming 6-fold higher obesity prevalence compared to men (26.5% vs 4.3%) and 89.2% of participants with obesity were women. Abdominal obesity was high, at 44.3%. Haiti faces a paradox of an ongoing national food insecurity crises and a burgeoning obesity epidemic. Individual, social, and environmental drivers of obesity, especially among women, need to be identified.